Immunogenicity of Hepavax-Gene recombinant hepatitis B vaccine in INML workers, Colombia (2007)
Objective: To evaluate the immunogenicity of Hepavax-Gene recombinant hepatitis B vaccine in INML workers since the last administered doses. Methods: Cross-sectional study on 603 health workers with at least three administered recombinant vaccine doses. Antibody levels (anti-HBs) were measured using the ELISA technique during December 2000 and January 2001, taking into account that the last dose in the vaccination varied between 1 and 6 years. Results: A total of 344 men and 259 women with an age mean of 38.8±7.3 years were studied. Protection levels were found in 90.7% (?10 U/1), decreasing significantly with the worker's age (p less than 0.00 1) and with the vaccine last dose administration time (p less than 0.01). Health workers with four doses compared to those with three doses had a 4.7% higher protection (antibody median 209.8 vs. 130.07, p less than 0.001). No association was found with gender (p=0.463), smoking (p=0.331) and blood exposure (p=0.433). Multivariate analyses found that no protection associated only with age (40-44 years HR=2.37, Cl 95%:1.18,4.78 and ?45 years HR=3.58, Cl 95%: 1.83,6.99). Conclusions: Although Hepavax-Gene recombinant hepatitis B vaccine (anti-HBs) has a high effectiveness in the health workers (90.7%) it presents a decrease in protection levels related to a higher worker's age and along vaccine last dose administration time. © 2007 Corporación Editora Médica del Valle.